John Paul Frank papers - Frank, John P. (John Paul), 1917-2002.
Correspondence, memoranda, a legislative bill, notes, photographs, speeches, and writings chiefly documenting Frank's relationship as a law clerk and friend of Supreme Court justice Hugo LaFayette Black which led to Frank's book Inside Hugo L. Black: The Letters (2000). Includes material pertaining to attempts to desegregate American law schools and to creation of an intermediate court of appeals to assist in reducing the work of the U.S. Supreme Court. Correspondents include Elizabeth Black and William H. Rehnquist.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Author, lawyer, and educator. Died 2002.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Black, Elizabeth -- Correspondence; Black, Hugo LaFayette, -- 1886-1971.; Rehnquist, William H., -- 1924-2005 -- Correspondence; United States. -- Congress. -- House. -- Committee on the Judiciary; United States. -- Supreme Court; Yale Law School -- Faculty; Appellate courts -- United States; Judges -- United States -- Biography; Segregation in higher education; Authors; Educators; Lawyers